Peningkatkan Motivasi Belajar IPA Melalui Pembelajaran Kooperatif Tipe Numbered Heads Together Pada Siswa SD - Rizalul Fiqry; Muhammad Fuadi; Asriyadin Asriyadin; Elsa Napisah; Nurnamira Nurnamira (Bima Journal of Elementary Education, 2024)
This study aimed to enhance the motivation to learn Science through the application of the Numbered Heads Together (NHT) cooperative learning model among fifth-grade students at SDN Inpres Pandai. The research methodology employed was classroom action research, involving 20 students as research subjects. The NHT model was implemented through several steps: dividing students into small groups based on numbers, posing questions to students with the same number in each group according to the current study material, collaborating within groups to find answers, and selecting one number from each group to present their group's answer. The research findings indicated an increase in learning motivation from 53.5% in the first cycle to 75.14% in the second cycle, marking an improvement of 21.64%. Furthermore, there was an enhancement in the completeness of learning outcomes from 60% in the first cycle (with a pretest of 0% and a posttest of 60%) to 80% in the second cycle (with a pretest of 40% and a posttest of 80%), reflecting a 20% increase. In conclusion, the use of the NHT model successfully increased both the motivation to learn and the completeness of science learning outcomes among fifth-grade students at SDN Inpres Pandai